From Marketplace to Parliament: Converting Digital Business Capital into Political Agency among Indonesian Female Candidates - Hendika Dwinanda Wicaksana; Budi Setiyono; Rina Martini; Hapsari Dwiningtyas Sulistyani; Deanda Dewindaru; Ade Indriani Siagian; Agnes Monica Marpaung; Fitria Hani Aprina; Moh. Yamin Darsyah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2026)
The 2024 Indonesian General Election saw a surge of “Mompreneur-Politicians”- female candidates who leveraged their micro-entrepreneurial background to boost their electoral appeal. This study employs a netnographic analysis of TikTok and Instagram to explore how they operate within the digital attention economy. Drawing upon Pierre Bourdieu’s theory of capital conversion and Deniz Kandiyoti’s concept of patriarchal bargaining, it argues that the Mompreneur identity converts commercial credibility into political trust. The findings suggest a “algorithmic campaigning” approach that combines soft-sell business stories with political messaging, which leads to increased audience engagement in comparison to traditional campaigning. This strategy offers women an alternative path outside of dynastic politics, but at the same time it reproduces patriarchal norms by legitimating political ambition through domesticity and service, and it commodifies democratic citizenship through increasingly clientelist-consumerist relations between voters and politicians.